Effect of Gas Injection in Pressure Restart of Waxy Crude Oil in the Pipeline for Different Timings After Pump Shutdown - Syed Nasruddin, Syed Muhammad Asim bin Syed Nasruddin (Universiti Teknologi Petronas, 2021)
The purpose of this experiment highlights the study of the effect of different gas injection rates in pressure restart of waxy crude oil in the pipeline. With many discoveries of crude oil reservoirs deep underneath the seabed in recent years, oil and gas operators have found many technical and operational challenges in trying to recover the heavy crude oil.